If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5 + z)(4z + 1) = 0 Reorder the terms: (5 + z)(1 + 4z) = 0 Multiply (5 + z) * (1 + 4z) (5(1 + 4z) + z(1 + 4z)) = 0 ((1 * 5 + 4z * 5) + z(1 + 4z)) = 0 ((5 + 20z) + z(1 + 4z)) = 0 (5 + 20z + (1 * z + 4z * z)) = 0 (5 + 20z + (1z + 4z2)) = 0 Combine like terms: 20z + 1z = 21z (5 + 21z + 4z2) = 0 Solving 5 + 21z + 4z2 = 0 Solving for variable 'z'. Factor a trinomial. (5 + z)(1 + 4z) = 0Subproblem 1
Set the factor '(5 + z)' equal to zero and attempt to solve: Simplifying 5 + z = 0 Solving 5 + z = 0 Move all terms containing z to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + z = 0 + -5 Combine like terms: 5 + -5 = 0 0 + z = 0 + -5 z = 0 + -5 Combine like terms: 0 + -5 = -5 z = -5 Simplifying z = -5Subproblem 2
Set the factor '(1 + 4z)' equal to zero and attempt to solve: Simplifying 1 + 4z = 0 Solving 1 + 4z = 0 Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 4z = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 4z = 0 + -1 4z = 0 + -1 Combine like terms: 0 + -1 = -1 4z = -1 Divide each side by '4'. z = -0.25 Simplifying z = -0.25Solution
z = {-5, -0.25}
| -7(v+4)+3v+7=8v+6 | | 4x=11.4285 | | 60+6x=70+4x | | a+(a+15)=265 | | 3e^2+5e= | | 14(v+4)-2v=4(3v+2)-16 | | 8x-7=19+15+7 | | 9t-54=126 | | 4(x+3)-3=13 | | -3x-(x-6)=-6-4(5-x) | | (8-w)(3w+1)=0 | | -6(4x-5)=3(4x-4)+78 | | x+3=2xlog*6 | | m^2-1+2m=0 | | 3(x+2)(x+3)=0 | | 4x^2-3x=24-(3x-1) | | 5/14/5/6= | | 0.25(x+30)-0.03(x-20)=5.9 | | 4-4[4-(6y-2)]= | | 1/3x-2=-12 | | -10(x+7)+529=15+24 | | 6(2x-3)+9x= | | 2y+x=153 | | (2a+b)(5a-3)= | | 139+x+14=180 | | 3x-3x-2=-2 | | 5M-3(2M+7)=3M+12-5M | | 58+6x+2=180 | | H=-16t+52t+7 | | 110+3x+16=180 | | -m/5=5/2 | | 85+6x+5=180 |